2023
DOI: 10.1155/2023/1500032
|View full text |Cite
|
Sign up to set email alerts
|

Green Coffee Bean Extract Potentially Ameliorates Liver Injury due to HFD/STZ-Induced Diabetes in Rats

Abstract: The goal of the current study was to examine the therapeutic potential of green coffee bean extract (GCBE) in the treatment of diabetic hepatic damage induced by high-fat diet (HFD) and streptozotocin (STZ) administration. The novelty of this study lies in constructing a newly stabilized in vivo obese diabetic animal model in rats using HFD/STZ for investigating the dose-dependent effect of two commonly used doses of GCBE in hepatoprotection against oxidative stress-induced hepatic damage by measuring many par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…This value was about 30% lower than that reported for non-defective green coffee beans (9.42 g CGAE/100 g dw) [ 57 ]. In a recent study with obese diabetic rats, Abdel-Mohsen et al [ 58 ] observed that an aqueous extract of non-defective green coffee beans rich in phenolic compounds exhibited hepatoprotective activity against oxidative-stress-induced damage. Although defective coffee beans have a lower TFC than non-defective green coffee beans, it is still high and this by-product could be used to investigate hepatoprotective activity as well as other pharmacological activities.…”
Section: Resultsmentioning
confidence: 99%
“…This value was about 30% lower than that reported for non-defective green coffee beans (9.42 g CGAE/100 g dw) [ 57 ]. In a recent study with obese diabetic rats, Abdel-Mohsen et al [ 58 ] observed that an aqueous extract of non-defective green coffee beans rich in phenolic compounds exhibited hepatoprotective activity against oxidative-stress-induced damage. Although defective coffee beans have a lower TFC than non-defective green coffee beans, it is still high and this by-product could be used to investigate hepatoprotective activity as well as other pharmacological activities.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the development of an alternative medical supply derived from natural products or plant-based sources is of utmost importance as it will facilitate the creation of innovative pharmaceuticals without any adverse effects [ [26] , [27] , [28] , [29] , [30] , [31] , [32] ]. Numerous natural products possess the ability to reduce weight and combat obesity caused by dietary factors.…”
Section: Introductionmentioning
confidence: 99%